2022
DOI: 10.1186/s12931-022-02171-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs participated in hypoxic pulmonary hypertension

Abstract: Background: Hypoxic pulmonary hypertension (HPH) is a common complication of chronic lung disease, which severely affects the survival and prognosis of patients. Several recent reports have shown that DNA damage and repair plays a crucial role in pathogenesis of pulmonary arterial hypertension. DNA-dependent protein kinase catalytic subunit (DNA-PKcs) as a part of DNA-PK is a molecular sensor for DNA damage that enhances DSB repair. This study aimed to demonstrate the expression and potential mechanism of DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Emerging evidence has suggested an involvement of DNA-PKcs in the pathogenesis of cardiovascular diseases including cardiac ischemia perfusion injury [ 14 ] and hypoxic pulmonary hypertension [ 39 ]. However, little is known with regards to the role of DNA-PKcs in Ang II-induced vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has suggested an involvement of DNA-PKcs in the pathogenesis of cardiovascular diseases including cardiac ischemia perfusion injury [ 14 ] and hypoxic pulmonary hypertension [ 39 ]. However, little is known with regards to the role of DNA-PKcs in Ang II-induced vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, our results showed that NU7441 markedly attenuated progression of vascular remodeling, and VSMC proliferative and migratory phenotypes. Of note, pharmacological inhibition of DNA-PKcs using NU7026 significantly attenuated PAH and neointima formation after wire-injury through suppressing neuron-derived orphan receptor (NOR1)-mediated VSMC proliferation [ 39 , 44 ]. These data indicated that targeting DNA-PKcs might be a new avenue for the treatment of vascular proliferative diseases, although DNA-PKcs played an important role in DNA quality control.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular diseases, DNA-PKcs contributes to endothelial dysfunction and atherosclerosis [16]. It influences the balance between endothelial repair and injury, and modulates inflammatory responses in atherosclerotic plaques [17]. This dual role of DNA-PKcs in both myocardial and vascular pathology marks it as a critical factor in the broader spectrum of cardiovascular diseases, offering a novel avenue for targeted therapies.…”
Section: Introductionmentioning
confidence: 99%